2020
DOI: 10.3390/antiox9020155
|View full text |Cite
|
Sign up to set email alerts
|

Biological Redox Impact of Tocopherol Isomers Is Mediated by Fast Cytosolic Calcium Increases in Living Caco-2 Cells

Abstract: Most of the biological impacts of Vitamin E, including the redox effects, have been raised from studies with α-tocopherol only, despite the fact that tocopherol-containing foods carry mixed tocopherol isomers. Here, we investigated the cellular mechanisms involved in the immediate antioxidant responses evoked by α-, γand δ-tocopherol in Caco-2 cells. In order to track the cytosolic redox impact, we performed imaging on cells expressing HyPer, a fluorescent redox biosensor, while cytosolic calcium fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Vitamin E has been actively investigated for its effects in managing pre-eclampsia, because it could tackle several pathophysiological pathways of the disease, theoretically. Firstly, vitamin E is a well-established antioxidant [ 45 , 46 ] that can suppress the oxidative damage caused by repeated placental ischaemia/reperfusion. Secondly, vitamin E and its metabolites are anti-inflammatory agents [ 47 , 48 , 49 ] that could suppress systemic inflammation caused by the release of damage-associated molecules.…”
Section: Vitamin E: Tocopherol and Tocotrienolmentioning
confidence: 99%
“…Vitamin E has been actively investigated for its effects in managing pre-eclampsia, because it could tackle several pathophysiological pathways of the disease, theoretically. Firstly, vitamin E is a well-established antioxidant [ 45 , 46 ] that can suppress the oxidative damage caused by repeated placental ischaemia/reperfusion. Secondly, vitamin E and its metabolites are anti-inflammatory agents [ 47 , 48 , 49 ] that could suppress systemic inflammation caused by the release of damage-associated molecules.…”
Section: Vitamin E: Tocopherol and Tocotrienolmentioning
confidence: 99%
“…In colon cancer cell lines, TFs were found to exhibit an anti-inflammatory effect and promoted apoptosis (especially δ-TF) in an IFNγ/PMA model [ 87 ], suppressing the activation of NF-κB (α-TF and γ-TF) and enhancing the Nrf2 pathway (δ-TF) [ 88 ]; their overall effect on antioxidant defense also seemed to be dependent on an elevation of cytoplasmic Ca 2+ [ 89 ]. Moreover, γ-TF increased PPARγ mRNA and protein expression (more efficiently versus α-TF or troglitazone), with possibly important implications in inflammatory diseases [ 90 ].…”
Section: Molecular and Cellular Mechanism Of Actionmentioning
confidence: 99%
“…Tocopherol and cyclodextrin have been reported to be used as therapeutic small drugs to alleviate lipid accumulation and recuperate enlarged lysosomes in several LSDs as they enhance lysosomal exocytosis through increment of cytosolic and lysosomal Ca 2+ level [19]. The exact mechanism of action is unclear, but it was reported that tocopherol isomers evoked fast Ca 2+ responses with an increase in cytosolic Ca 2+ [20]. It was also shown that tocopherol caused exocytosis of related vesicles, such as endocytic ones [21].…”
Section: Introductionmentioning
confidence: 99%